Hypocretin (orexin) regulation of sleep-to-wake transitions - De Lecea, Luis; Huerta, Ramon (Frontiers in Pharmacology, 2014)
The hypocretin (Hcrt), also known as orexin, peptides are essential for arousal stability. Here I discuss background information about the interaction of Hcrt with other neuromodulators, including norepinephrine and acetylcholine probed with optogenetics. I conclude that Hcrt neurons integrate metabolic, circadian and limbic inputs and convey this information to a network of neuromodulators, each of which has a different role on the dynamic of sleep-to-wake transitions. This model may prove useful to predict the effects of orexin receptor antagonists in sleep disorders and other conditions.